UZBEK NATIONAL MUSICAL INSTRUMENTS: TRADITION, EVOLUTION, AND CULTURAL IDENTITY (American Journal of Interdisciplinary Research and Development, 2025)
Uzbekistan’s musical heritage is as diverse and vibrant as its landscape, reflecting centuries of cultural exchange along the ancient Silk Road. This article explores the rich tradition of Uzbek national musical instruments, examining their origins, construction, performance practices, and evolving roles in modern society. From the gentle strumming of the dutar to the commanding blasts of the karnay, each instrument is a living testament to the country’s history and cultural identity. We delve into the historical context, analyze individual instruments, and discuss the contemporary revival and fusion of these musical traditions, offering readers a comprehensive understanding of Uzbekistan’s sonic heritage.